Performance of sorghum and linseed intercropping system with different row proportion and planting geometry under rainfed condition: PERFORMANCE OF SORGHUM AND LINSEED INTERCROPPING UNDER RAINFED CONDITION - G V SHUBHA; S A BIRADAR; SATYANARAYNRAO; B G KOPPALKAR; M R GOVINDAPPA; K AJITHKUMAR; RAJANNA (Journal of Oilseeds Research, 2015)
Afield experiment was conducted atMain AgriculturalResearch Station,Raichur, Karnataka during rabiseason of 2013-14 under rainfed condition in medium black soil to study the yield performance and economics ofsorghum and linseed intercropping system with different row proportion and planting geometry. The results revealed that, among various intercropping systems, sorghum+linseed in 1:2 with 30 cm rows spacing recorded significantly highersorghum equivalent yield of 1822 kg/ha followed by chickpea+ linseed in 2:1 with 45 cm rows (1671 kg/ha) and sorghum+linseed in 1:1 with 30 cm rows (1653 kg/ha). The land equivalent ratio was significantly highest in sorghum+ linseed in 1:2 with 30 cmrows(1.70)followed by chickpea+linseed in 2:1 with 45 cmrows(1.10). Higher net returns was recorded in sorghum+linseed in 1:2 with 30 cm rows (` 34,348/ha) followed by sorghum+chickpea (2:1) 45 cm rows (` 31,211/ha) and sorghum+linseed (1:1) 30 cm rows (` 29,876/ha). However, higher B:C was recorded in sorghum+linseed (1:2) 30 cm rows (2.05).